Family firms and corporate spatial responsibilities in Germany: Implication for urban and regional planning and management - Hans-Hermann Albers; Lech Suwala (Family Business and Regional Development, 2021)
By connecting the two evolving discourses on family firms in spatial contexts and corporate spatial responsibilities, this chapter introduces a unique perspective on family firm-driven urban and regional engagement. This chapter summarizes selected existing case studies of family firm-driven urban and regional engagement from literature and asks how and to what extent family firms implement corporate spatial initiatives. In other words, whether family firms are spatially responsible.
Keywords: R58; R11; R12; L52; L53; O20; 330; Family Firms; Regional Development; Corporate Social Responsibility; Corporate Spatial Responsibility; Urban and Regional Planning; Private-Sector Led Development; Business Improvement Districts; Town-Center Management; Family Firm-led Master Plan Initiatives